2020
DOI: 10.1146/annurev-micro-012120-063427
|View full text |Cite
|
Sign up to set email alerts
|

Surface Sensing and Adaptation in Bacteria

Abstract: Bacteria thrive both in liquids and attached to surfaces. The concentration of bacteria on surfaces is generally much higher than in the surrounding environment, offering bacteria ample opportunity for mutualistic, symbiotic, and pathogenic interactions. To efficiently populate surfaces, they have evolved mechanisms to sense mechanical or chemical cues upon contact with solid substrata. This is of particular importance for pathogens that interact with host tissue surfaces. In this review we discuss how bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 217 publications
0
56
0
Order By: Relevance
“…Consequently, the ability to sense a surface is crucial for bacteria during this process. Surface sensing can be facilitated passively by membrane associated proteins that sense the presence of a surface upon contact or actively by obstruction of the motion of an extracellular appendage [4][5][6][7][8][9]. For example, flagella are long helical appendages that generate a propulsive force that enable bacteria to swim in liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the ability to sense a surface is crucial for bacteria during this process. Surface sensing can be facilitated passively by membrane associated proteins that sense the presence of a surface upon contact or actively by obstruction of the motion of an extracellular appendage [4][5][6][7][8][9]. For example, flagella are long helical appendages that generate a propulsive force that enable bacteria to swim in liquid.…”
Section: Introductionmentioning
confidence: 99%
“…T4P are also involved in surface attachment and biofilm formation, which are important in the life of many prokaryotes. Biofilms confer a fitness advantage over planktonic solitary cells by protection from diverse environmental stresses, better nutrient availability and drug and predator resistance (Laventie & Jenal, 2020). Surface recognition by different appendages, including T4P, triggers signal transduction cascades involving second messengers, quorum‐sensing systems, two‐component systems and small regulatory RNAs (Laventie & Jenal, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms confer a fitness advantage over planktonic solitary cells by protection from diverse environmental stresses, better nutrient availability and drug and predator resistance (Laventie & Jenal, 2020). Surface recognition by different appendages, including T4P, triggers signal transduction cascades involving second messengers, quorum‐sensing systems, two‐component systems and small regulatory RNAs (Laventie & Jenal, 2020). For Pseudomonas , which possesses T4aP and a single polar flagellum, it was suggested that pilus tension leads to conformational change of the T4P, which subsequently leads to 3ʹ,5ʹ‐cyclic adenosine monophosphate (cAMP) production and activation of virulence programmes (Persat et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…T4P are also involved in surface attachment, which is an important part in the life of prokaryotes, enabling biofilm formation. Thus, biofilms confer a fitness advantage over planktonic solitary cells by protection from diverse environmental stresses, better nutrient availability and drug and predator resistance (Laventie and Jenal, 2020). Surface recognition by different appendages, including T4P, triggers signal transduction cascades involving second messengers, quorum-sensing systems, two-component systems and small regulatory RNAs (Laventie and Jenal, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biofilms confer a fitness advantage over planktonic solitary cells by protection from diverse environmental stresses, better nutrient availability and drug and predator resistance (Laventie and Jenal, 2020). Surface recognition by different appendages, including T4P, triggers signal transduction cascades involving second messengers, quorum-sensing systems, two-component systems and small regulatory RNAs (Laventie and Jenal, 2020). For Pseudomonas, which possesses T4P and a single polar flagellum, it was suggested that pilus tension leads to conformational change of the T4P, which subsequently leads to 3',5'-cyclic adenosine monophosphate (cAMP) production and activation of virulence programmes (Persat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%